Fabrication and Implementation of PVA Thin Film-based Relative Humidity Sensor - Al-haddar, Mohammed Taha Omar; Sin, Yew-Keong (International Journal of Integrated Engineering, 2024)
This paper presents the fabrication of polyvinyl alcohol (PVA)-based relative humidity sensors using copper interdigitated electrodes (IDEs). These sensors were fabricated by patterning copper IDEs onto FR4 fiberglass substrates and coating them with a thin film of PVA. By varying the number of IDE electrode pairs and the concentration of PVA, the sensors exhibited different resistance values, demonstrating an inverse relationship with the number of IDE electrodes and PVA concentration. Additionally, the thickness of the sensing layer, controlled by spin coating speed, affected the resistance of the sensors. The fabricated sensors achieved a humidity measurement range from 50% to 99% RH based on resistance changes. Furthermore, an interface circuit was designed to integrate the fabricated sensors with an ESP8266 microcontroller, achieving accurate measurements above 74% RH.